German military expansion in Europe and the American position on it (1941-1939) (Journal of the College of Basic Education, 2024)
Based on the importance of Germany in the American strategy, this research was chosen, which addresses, albeit briefly, the American administration’s position on German military expansion in Europe 1939-1941, as the first date represented the outbreak of World War II, following Germany’s occupation of Poland. While the second date represented the entry of the United States of America into World War II and its impact on the course of the war.In light of this, the research was divided into three main axes. The first dealt with the policy of the United States of America regarding German expansion in Europe for the period (1933-1938), while the second axis touched on the position of the American administration regarding the German occupation of Poland in 1939, while the third axis discussed the entry of the United States. United States of America World War II in 1941 and the German position on it.